2023 Consolidated Technical and Financial Report for Independent Advisory and Evaluation Service (IAES), Independent Science for Development Council (ISDC), and Standing Panel on Impact Assessment (SPIA) - CGIAR Independent Advisory and Evaluation Service (2024)
The 2023 efforts of ISDC, SPIA, and IAES/Evaluation Function, underpinned by IAES operational support, reflect a productive year providing independent advising and evaluative and impact evidence in CGIAR's research and innovation landscape. These entities’ dedication to inclusivity, knowledge sharing, and effective governance helps to position them for continued success in the coming years.